MODELING OF LAND VALUE IN KARST AREA FOR IMPOSITION LAND AND BUILDING TAX IN THE MINING SECTOR - WAHJU WIDODO (NIM 25106026), HARRIS
The tax imposed on the mining business at karst area do not yet considering environmental destruction factor possibly caused. For that it is required an attempt to make safe the karst area in addition to take the benefit of the mining conducted. The regulernd function of the tax can be applied to the karst area through the imposition land property tax for the C class mining. The land valuating method that can be applied to the location of the C class mining at the karst area for supporting the control is by determining of NJOP specially by regarding the environmental factor. The objective of this research is to yield a land value model at the karst area using a valuating method considering the environmental factor using a multivariate analysis and a multi-criteria spatial decision supporting system in the form of economic, social and environmental criteria. Data analysis and the making of alternative model used a regression to the class of land values based on the weight provided by all interested parties for the karst area. The selection of model and analysis of model result by comparing the class of land values as a result of the modeling with the existing data and to accommodate the interest of the involved parties. The analysis of model application by comparing NJOP model to the existing NJOP and the mounts of principle PBB model to the existing PBB. The result of analysis shows that the model of land value at the karst area is Y = 0,016 - 0,217(X1) - 0,103(X2) + 0,19(X3) - 0,114(X4) - 0,087(X5) + 0,121(X6) with the value of R2 is 0.922 meaning 92.2% of the land value can be explained by the model. The result of modeling can improves the class of land values and it can increase the potency of PBB provision for the mining object of the C class mining more than 600%.